Authorial Subjectivity in Salman Rushdie’s Fury and Quichotte - Trajanka Kortova Jovanovska (Études Britanniques Contemporaines, 2025)
In his extensive oeuvre, Salman Rushdie foregrounds the question of authorship by means of figures of writers and writing subjects who contemplate and reflect on the nature and purpose of their craft, their authorial identity and their positioning in society and intellectual history in, through, and by means of, (their) writing. This article aims to explore the subjectivity of the author in Rushdie’s novels Fury and Quichotte. As opposed to a representation of the author as indelibly marked by his national and historical context, as in Midnight’s Children and The Moor’s Last Sigh, or by an ambivalent indeterminacy that precludes a final grounding of the self, as in The Satanic Verses, in these two novels the authorial self is formed almost exclusively in relation to the author’s fictional characters. By focusing on how an author situates himself in relation to his work’s afterlife, Fury and Quichotte portray an image of postcolonial authorship in which the postcolonial author opts for the in-between space of exile or advances fiction itself as a necessary component of his self.